Second-Tier Next Generation Sequencing Integrated in Nationwide Newborn Screening Provides Rapid Molecular Diagnostics of Severe Combined Immunodeficiency - Strand, Janne; Gul, Kiran Aftab; Erichsen, Hans Christian; Lundman, Emma; Berge, Mona C.; Trømborg, Anette K.; Sørgjerd, Linda K.; Ytre-Arne, Mari; Hogner, Silje; Halsne, Ruth; Gaup, Hege Junita; Osnes, Liv T.; et al. (Frontiers in Immunology, 2020)
Severe combined immunodeficiency (SCID) and other T cell lymphopenias can be detected during newborn screening (NBS) by measuring T cell receptor excision circles (TRECs) in dried blood spot (DBS) DNA. Second tier next generation sequencing (NGS) with an amplicon based targeted gene panel using the same DBS DNA was introduced as part of our prospective pilot research project in 2015. With written parental consent, 21 000 newborns were TREC-tested in the pilot. Three newborns were identified with SCID, and disease-causing variants in IL2RG, RAG2, and RMRP were confirmed by NGS on the initial DBS DNA. The molecular findings directed follow-up and therapy: the IL2RG-SCID underwent early hematopoietic stem cell transplantation (HSCT), without any complications; the leaky RAG2-SCID received prophylactic antibiotics, antifungals, and immunoglobulin infusions, and underwent HSCT at 1 year of age. The child with RMRP-SCID had complete Hirschsprung and died at 1 month of age. Since January 2018, all newborns in Norway have been offered NBS for SCID using 1st tier TRECs and 2nd tier gene panel NGS on DBS DNA. During the first 20 months of nationwide SCID screening an additional 88 000 newborns were TREC tested, and four new SCID cases were identified. Disease-causing variants in DCLRE1C, JAK3, NBN, and IL2RG were molecularly confirmed on day 8, 15, 8 and 6, respectively after birth, using the initial NBS blood spot. Targeted gene panel NGS integrated into the NBS algorithm rapidly delineated the specific molecular diagnoses and provided information useful for management, targeted therapy and follow-up i.e X rays and CT scans were avoided in the radiosensitive SCID. Second tier targeted NGS on the same DBS DNA as the TREC test provided instant confirmation or exclusion of SCID, and made it possible to use a less stringent TREC cut-off value. This allowed for the detection of leaky SCIDs, and simultaneously reduced the number of control samples, recalls and false positives. Mothers were instructed to stop breastfeeding until maternal cytomegalovirus (CMV) status was determined. Our limited data suggest that shorter time-interval from birth to intervention, may prevent breast milk transmitted CMV infection in classical SCID.